2
$\begingroup$

Let $X$~$\Gamma(\alpha,\lambda)$ and $Y$~ $\Gamma(\beta,\lambda)$, where $\Gamma(r,\lambda)$ denotes the Gamma distribution with density $f_{r,\lambda}(x)=\lambda e^{-\lambda x}\frac{(\lambda x)^{r-1}}{\Gamma(r)}\mathbb{1}_{[o,\infty)}(x)$ for $\lambda >0, r>0$. Denoting by $f_X$ the density of $X$ and $f_Y$ the density of $Y$, assume that the density of $(X,Y)$ is $f_X\cdot f_Y$.Define $Z=X+Y$ and $U=\frac X{X+Y}$

  1. Show that the density of $(Z,U)$ can be written as the product of two densities.
  2. Compute the density of $U$

What I did so far:

For 1: We have $f_X(x)=\lambda e^{-\lambda x}\frac{(\lambda x)^{\alpha -1}}{\Gamma(\alpha)}\mathbb{1}_{[o,\infty)}(x)$ and similarly $f_Y(y)=\lambda e^{-\lambda y}\frac{(\lambda y)^{\beta -1}}{\Gamma(\beta)}\mathbb{1}_{[o,\infty)}(y)$. Hence $f_{(X,Y)}=\lambda^2e^{-\lambda(x+y)}\frac{(\lambda x)^{\alpha -1}(\lambda y)^{\beta -1}}{\Gamma(\alpha)\Gamma(\beta)}\mathbb{1}_{[o,\infty)}(x)\mathbb{1}_{[o,\infty)}(y)=\lambda^{\alpha+\beta}e^{-\lambda(x+y)}\frac{x^{\alpha-1}y^{\beta-1}}{\Gamma(\alpha)\Gamma(\beta)}\mathbb{1}_{[o,\infty)}(x)\mathbb{1}_{[o,\infty)}(y)$

Then form the application $g(x,y)=(x+y,\frac x{x+y})=(z,u)$ we find its inverse to be $g^{-1}(z,u)=(zu,z(1-u))$ such that the Jacobian matrix is $J_{g^{-1}}(z,u)= \begin{pmatrix}u&1-u \\z&-z \end{pmatrix} \Rightarrow |\det(J_{g^{-1}}(z,u))|=|-z|=z$

So we have $f_{(Z,U)}(z,u)=f_{(X,Y)}(zu,z(1-u))|\det(J_{g^{-1}}(z,u))|=\frac{\lambda^{\alpha+\beta}}{\Gamma(\alpha)\Gamma(\beta)}e^{-\lambda z}z^{\alpha+\beta-1}u^{\alpha-1}(1-u)^{\beta-1}\mathbb{1}_{[o,\infty)}(z)\mathbb{1}_{[o,\infty)}(u)$

How can I say that this is a product of two densities? I don't know if the request is ambiguos or maybe do I miss something?

For 2: $f_U(u)=\frac{\lambda^{\alpha+\beta}}{\Gamma(\alpha)\Gamma(\beta)}u^{\alpha-1}(1-u)^{\beta-1}\int_0^\infty e^{-\lambda z}z^{\alpha+\beta-1} dz$

Since the integral using just partial integration seems to be infinite to compute, I used a calculator which returned that$\int_0^\infty e^{-\lambda z}z^{\alpha+\beta-1} dz=-\lambda^{-\alpha-\beta}\Gamma(\alpha+\beta,\lambda z)$.

Now this can be true, but we've never seen this "incomplete gamma function", so I was a litlle concerned about this result, is there a "smoother" way to compute it?

$\endgroup$
1
2
$\begingroup$

Divide and multiply by the term $\Gamma(\alpha+\beta)$ in your completed density $f(Z, U)$ to get

$$f(Z, U)=\frac{\lambda^{\alpha+\beta}}{\Gamma(\alpha+\beta)}z^{\alpha+\beta-1}e^{-\lambda z}\frac{\Gamma(\alpha+\beta)}{\Gamma(\alpha)\Gamma(\beta)}u^{\alpha-1}(1-u)^{\beta-1}, z>0, 0<u<1$$

As you can see this has been factored into the product of a $\text{Gamma}(\alpha+\beta,\lambda)$ density and a $\text{Beta}(\alpha,\beta)$ density.

Thus $U\sim\text{Beta}(\alpha,\beta)$ with density shown.

At this point we have answered both problems.

You could also integrate out the $Z$ to find the density of $U$ (not necessary as they are independent), in which case notice that $$\int_0^\infty z^{\alpha+\beta-1}e^{-\lambda z}=\frac{\Gamma(\alpha+\beta)}{\lambda^{\alpha+\beta}}$$

and we would end up with the density of the beta distribution (but again, was not necessary here as the joint density is factorizable into a function of $U$ and a function of $Z$)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.